Internalisasi Lembaga Dakwah Raodatul Mujaddid Terhadap Kecerdasan Spritual Bagi Mahasiswa Fakultas Teknik Universitas Negeri Makassar - Nurmila Nurmila; Lahming Lahming; Amirah Mustarin (Seminar Nasional LP2M UNM, 2019)
This study aims to obtain a picture related to the internalization of the Raodatul Mujaddid institute on spiritual intelligence for students at the Faculty of Engineering, Makassar State University and to make suggestions on classical guidance topics to improve students' spiritual intelligence. This research is a descriptive research with survey method. The research subjects consisted of 50 people taken with a simple randomized system that is homogeneous. The research instrument used was a questionnaire that revealed things that were internal to the Da'wah Raodatul Mujaddid Institute of Engineering at the Makassar State University related to the level of spiritual intelligence of students which included several signs of spiritual intelligence, namely flexible, high awareness, ability to deal with suffering , the ability to deal with pain, the quality of life inspired by a vision based on norms and unwillingness to do harmful things, and a tendency to be independent. The data analysis technique used is the categorization of students' intelligence at the Makassar State University Faculty of Engineering based on Azwar's criteria, that there are three levels of student intelligence, namely, low, medium and high. The results showed that with the activities carried out by the Da'wah Raodatul Mujaddid Mentors, there were no 2018-2019 students who had low intelligence, but from the research subjects who were respondents that 29 students had moderate intelligence and 21 students who have a high level of intelligence. Based on the distributed questionnaire items showed that the level of intelligence of students in general is still in the medium category so that researchers propose classical guidance that is appropriate for their improvement.